Phoneme Segmentation Based on Wavelet Spectra Analysis - ZIÓŁKO, Bartosz; MANANDHAR, Suresh; WILSON, Richard C.; ZIÓŁKO, Mariusz (Archives of Acoustics, 2011)
A phoneme segmentation method based on the analysis of discrete wavelet transformspectra is described. The localization of phoneme boundaries is particularlyuseful in speech recognition. It enables one to use more accurate acoustic modelssince the length of phonemes provide more information for parametrization.Our method relies on the values of power envelopes and their first derivatives forsix frequency subbands. Specific scenarios that are typical for phoneme boundariesare searched for. Discrete times with such events are noted and graded usinga distribution-like event function, which represent the change of the energy distributionin the frequency domain. The exact definition of this method is described inthe paper. The final decision on localization of boundaries is taken by analysis ofthe event function. Boundaries are, therefore, extracted using information from allsubbands. The method was developed on a small set of Polish hand segmented wordsand tested on another large corpus containing 16 425 utterances. A recall and precisionmeasure specifically designed to measure the quality of speech segmentationwas adapted by using fuzzy sets. From this, results with F-score equal to 72.49%were obtained.